Bring Them All Home: The Hostage Return Protests and Making of Israeli Foreign Policy in the October 7th War - Tucakov, Nikola (Political Life, 2025)
The article presents an analysis of the role of protests aimed at the return of Israeli hostages as a key factor in setting the foreign policy agenda of the State of Israel during the first two years of the October 7th War. By relying on Robert Putnam’s ‘two-level’ approach to foreign policy analysis, the protesters, both as organised groups and regular citizens, are viewed as key actors in the ‘second’, i.e. domestic level of politics. By demonstrating the importance of protests in setting the agenda for warfare and peace negotiations, as well as their limitations in this regard, the article argues for a continued analytical relevance of popular mobilization within Israel’s political system and foreign policy. In particular, the ability of protests to set and maintain the return of the hostages as war goal, yet their inability to effect a ceasefire deal, is placed in the context of Israel’s political pluralism and democratic procedures.